Using all-phase Fourier method to reconstruct discontinuous signal - HUANG Xiang-dong; WANG Zhao-hua; LI Wen-yuan (Tongxin xuebao)
In order to reconstruct discontinuous signal with the least error by using finite information, the concept of all-phase data processing and the conventional Fourier approximation were combined. By utilizing the coefficients acquired by discrete Fourier transforming the samples of signal and the high harmonic information, all-phase Fourier reconstruction was formed. Theoretical deduction and experimental research show that the waveform reconstructed by all-phase Fourier method has less error than those constructed by conventional continuous Fourier integral approximation and the discrete Fourier reconstruction.